Airway pressure and outcome of out-of-hospital cardiac arrest: A prospective observational study. (January 2017) - Chalkias, Athanasios; Pavlopoulos, Fotios; Koutsovasilis, Anastasios; d'Aloja, Ernesto; Xanthos, Theodoros
Abstract: Aim: To assess the usefulness of airway pressure as predictor of return of spontaneous circulation (ROSC), as well as to investigate the optimized ventilation compression strategy during cardiopulmonary resuscitation (CPR). Methods: In this prospective observational study, 300 out-of-hospital cardiac arrest victims were intubated and resuscitated with the use of a ventilator. Mean airway pressure (mPaw) was measured at pre-defined phases of CPR. Results: A significant difference in mPaw was observed between survivors and non-survivors after the onset of the third minute of CPR. An mPaw value of 42.5 mbar during CPR had specificity and sensitivity of 0.788 and 0.804, respectively, for ROSC (AUC = 0.668, p = 0.047). During CPR, we found statistically significant differences in mPaw at phases zero (F = 4.526, p = 0.002), two (F = 4.506, p = 0.002), four (F = 8.187, p < 0.0001), five (F = 2.871, p = 0.024), and six (F = 5.364, p < 0.0001). Conclusion: Mean airway pressure was higher in survivors. A value of 42.5 mbar was associated with ROSC.